2017
DOI: 10.1186/s13756-017-0180-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-existence of bla OXA-23 and bla NDM-1 genes of Acinetobacter baumannii isolated from Nepal: antimicrobial resistance and clinical significance

Abstract: BackgroundMolecular analysis of carbapenem-resistant genes in Acinetobacter baumannii, an emerging pathogen, is less commonly reported from Nepal. In this study we determined the antibiotic susceptibility profile and genetic mechanism of carbapenem resistance in clinical isolates of A. baumannii. Methods A. baumannii were isolated from various clinical specimens and identified based on Gram staining, biochemical tests, and PCR amplification of organism specific 16S rRNA and bla OXA-51 genes. The antibiotic sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 35 publications
(41 reference statements)
10
63
1
Order By: Relevance
“…Coexistence of bla NDM-1 and bla OXA-48 carrying plasmids was reported in an isolate of K. pneumoniae from China [72]. Similarly, coexistence of bla NDM-1 and bla OXA-23 was reported in A. baumannii from Nepal [73]. K. pneumoniae of type 11 was reported in Greek to be coproducing two metallo beta-lactamses markers, NDM-1 and VIM-1 together [74].…”
Section: Introductionmentioning
confidence: 97%
“…Coexistence of bla NDM-1 and bla OXA-48 carrying plasmids was reported in an isolate of K. pneumoniae from China [72]. Similarly, coexistence of bla NDM-1 and bla OXA-23 was reported in A. baumannii from Nepal [73]. K. pneumoniae of type 11 was reported in Greek to be coproducing two metallo beta-lactamses markers, NDM-1 and VIM-1 together [74].…”
Section: Introductionmentioning
confidence: 97%
“…the isolate showing DDST + bla VIM + bla GIM positivity. In an earlier study from Nepal, co-existence of bla OXA-23 and bla NDM-1 was detected [45] with the presence of other class B MBLs, such as bla VIM and bla GIM . One of the recent studies showed the presence of bla VIM only in imipenem-resistant genomic species of 13TU -A. baumannii and not in other isolates [46].…”
Section: Discussionmentioning
confidence: 81%
“…ESBL production might be due to the presence of ESBL producing genes like bla OXA-23 and antibiotic genes that can be transferred to other bacteria horizontally through conjugation and due to excessive use of broad spectrum antibiotics (Joshi et al 2017;Shrestha et al 2017). The acquisition of MBL-encoding genes such as vim1, vim2, imp1 and imp2 is one of the ways to acquire resistance to carbapenems like imipenem, meropenem and ertapenem (Davoodi et al 2015).…”
Section: Discussionmentioning
confidence: 99%